Lattice paths and N-color partitions - Agarwal A.K. (Utilitas Mathematica, 1998)
Recently, we interpreted combinatorially some q-identities from Slater's compendium by using n-color partitions. In this paper we use lattice paths to give a different combinatorial meaning to the same q-identities. This leads to six new combinatorial identities involving lattice paths and n-color partitions.